ANALISIS LAPORAN KEUANGAN DI ERA DIGITAL - Pratiwi, Devica (Universitas Bunda Mulia, 2021)
ABSTRACT The rapid development of technology and increasingly high business competition poses a challenge for business people to always be quick and responsive to changes in order to decide on effective strategies to survive in the increasingly tight business world of the industrial world. In the world of accounting, a growing issue of the role of accountants will be replaced by technology. There was a shift in the function of the accountant from working manually to digitization in preparing financial reports and analysis based on the financial information generated. This service activity was carried out on March 16, 2020 in the computer lab room of Bunda Mulia University which consisted of Atisa Dipamkara Tangerang Vocational School students. The event took place from 09.00 - 11.00 starting with the introduction of accounting software, namely Accurate, the available tools and how to operate Accurate to produce financial reports quickly and accurately. Then the explanation is continued by reading the results of the financial statements to determine the merits of the company's performance in a certain period. The results of this activity can be seen from the enthusiasm of the participants with a discussion of questions and answers regarding accounting software and its comparison with the software they have studied at school, then asking about what financial information can be generated from the software and how to prepare accounting information to read the results in easy to understand. The implication of this service activity is that it can provide awareness for participants to be skilled in using technology in preparing financial information and developing soft skills as prospective accountants in communicating this information to interested parties.